6(-x-5)=-4(x-3)-x

Simple and best practice solution for 6(-x-5)=-4(x-3)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-x-5)=-4(x-3)-x equation:


Simplifying
6(-1x + -5) = -4(x + -3) + -1x

Reorder the terms:
6(-5 + -1x) = -4(x + -3) + -1x
(-5 * 6 + -1x * 6) = -4(x + -3) + -1x
(-30 + -6x) = -4(x + -3) + -1x

Reorder the terms:
-30 + -6x = -4(-3 + x) + -1x
-30 + -6x = (-3 * -4 + x * -4) + -1x
-30 + -6x = (12 + -4x) + -1x

Combine like terms: -4x + -1x = -5x
-30 + -6x = 12 + -5x

Solving
-30 + -6x = 12 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-30 + -6x + 5x = 12 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-30 + -1x = 12 + -5x + 5x

Combine like terms: -5x + 5x = 0
-30 + -1x = 12 + 0
-30 + -1x = 12

Add '30' to each side of the equation.
-30 + 30 + -1x = 12 + 30

Combine like terms: -30 + 30 = 0
0 + -1x = 12 + 30
-1x = 12 + 30

Combine like terms: 12 + 30 = 42
-1x = 42

Divide each side by '-1'.
x = -42

Simplifying
x = -42

See similar equations:

| 3x-5=2+12 | | x^2+1.78x^2=400 | | 5-x+2=3x-7 | | 8(t-3)+4t=6(2t+3)-13 | | x^2+.56x^2=400 | | x^2+.56x^2=20 | | 15x^4+29x^3-14x^2=0 | | y=1ox-3 | | 2x-8=(x+2) | | 5-3(x-2)=8-(4-2x) | | 89+84=78 | | 9b^3+15b^2-36b= | | 35=0.42*w | | 3b^3+15b^2-36b= | | 84++89+=78 | | 3.375=p*37.5 | | a+18=7 | | .35*w=42 | | (3/2)c+c=20 | | 6v^2-19+10= | | Y=2x^3-9x^2+10x-3 | | 24a^3-16a^2= | | w^2-14w+40= | | 6x^2+48x-73=0 | | t^2+3t-40= | | 2.5(x+8)=12.8+1.6x | | v^2+5v+4= | | 9/4=36 | | 7(t-6)+5t=6(2t+2)-10 | | x+3/4=20 | | 3p-10=15 | | 6t-4t+5t-3t= |

Equations solver categories